Beta-Thalassemia Major and Female Fertility: The Role of Iron and Iron-Induced Oxidative Stress - Paraskevi Roussou; Nikolaos J. Tsagarakis; Dimitrios Kountouras; Sarantis Livadas; Evanthia Diamanti-Kandarakis (Anemia)
Endocrine complications due to haemosiderosis are present in a significant number of patients with beta-thalassemia major (BTM) worldwide and often become barriers in their desire for parenthood. Thus, although spontaneous fertility can occur, the majority of females with BTM is infertile due to hypogonadotropic hypogonadism (HH) and need assisted reproductive techniques. Infertility in these women seems to be attributed to iron deposition and iron-induced oxidative stress (OS) in various endocrine organs, such as hypothalamus, pituitary, and female reproductive system, but also through the iron effect on other organs, such as liver and pancreas, contributing to the impaired metabolism of hormones and serum antioxidants. Nevertheless, the gonadal function of these patients is usually intact and fertility is usually retrievable. Meanwhile, a significant prooxidants/antioxidants imbalance with subsequent increased (OS) exists in patients with BTM, which is mainly caused by tissue injury due to overproduction of free radicals by secondary iron overload, but also due to alteration in serum trace elements and antioxidant enzymes. Not only using the appropriate antioxidants, essential trace elements, and minerals, but also regulating the advanced glycation end products, could probably reduce the extent of oxidative damage and related complications and retrieve BTM women’s infertility.